Evidence of impaired antigen non-specific but normal antigen specific suppressor cell function in children with autoimmune chronic active hepatitis. - Lobo-Yeo, A (1987)
In autoimmune chronic active hepatitis (aCAH), autoaggression is believed to derive from a defect in immunoregulation. Antigen non-specific Concanavalin A (Con A) induced suppressor cell function has been reported to be impaired. In 11 children with aCAH we have investigated inhibition of production of a specific antibody (anti-tetanus toxoid, anti-TT) by suppressor cells induced either by a non-specific stimulus (Con A) or by the specific antigen (tetanus toxoid, TT). Con A induced suppression of anti-TT was significantly lower in patients (15.7 +/- 2.5%) than in controls (46.7 +/- 4.4%; P less than 0.01). In contrast, high dose tetanus toxoid induced suppression was similar in patients and controls (69.8 +/- 4.2, 72.0 +/- 3.6%, respectively). Both groups had similar serum anti-TT levels and in vitro production of anti-TT in response to optimal dose of TT. Our data indicate that antibody production to a T cell-dependent antigen is under the control of at least two regulatory mechanisms, one antigen specific and one antigen non-specific, only the latter being defective in aCAH.